Analisis Leasing Syariah dan Leasing Konvensional : Studi Komparatif Terhadap Prinsip, Mekanisme, dan Implementasinya di Indonesia - Ai Nunung Nursamsyah; Dian Rosdiana; Yudi Agustiansyah; Iwan Wahdiana; Irfan Saepuloh (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This paper evaluates how effectively Islamic principles are integrated into non-bank financial institutions, with a specific focus on Sharia-compliant leasing companies. Relying on a literature review methodology, this study adopts a descriptive-analytical framework to examine a wide array of sources, including academic books, peer-reviewed journals, scholarly articles, and current Indonesian statutory regulations. The findings indicate that true Sharia compliance cannot be judged merely by the adoption of Islamic terminology in product offerings or contracts. The casual use of terms like mudharabah, musyarakah, or ijarah does not automatically guarantee that the actual operations align with Islamic jurisprudence. In practice, several self-labeled Sharia financing firms remain heavily driven by conventional profit-maximization goals. This profit-centric mindset often results in operational mechanisms that conflict with core Islamic values, such as the imposition of late fees or penalties that risk crossing into riba (usury). Consequently, the study emphasizes the need for continuous oversight and rigorous evaluation to ensure that Sharia leasing operations genuinely embody the principles of justice, transparency, and authentic compliance with Islamic law.